Erosion of a pollination mutualism along an environmental gradient in a south Andean treelet, Embothrium coccineum (Proteaceae) - Chalcoff, Vanina Ruth (2011)
Th e limit of a species ’ distribution can be determined biotically if an environmental gradient causes the loss of critical mutualists such as pollinators. We assessed this hypothesis for Embothrium coccineum , a self-incompatible red-fl owered treelet growing along a strong west-east precipitation gradient from rainforest to forest-steppe ecotone in the rain shadow of the southern Andes in northwestern Patagonia. For 16 populations along this gradient, we quantifi ed composition of the pollinator assemblage, pollination effi ciency and limitation, and reproductive output. Th e treelet has a generalized pollination system, but the hummingbird Sephanoides sephaniodes was the most eff ective pollinator. Th e relative importance of this hummingbird as a fl ower visitor within populations infl uenced pollen transfer and fruit set more strongly than local precipitation. As hummingbirds and other pollinators, including passerine birds and nemestrinid fl ies, were replaced by bees towards the dry eastern range limit, pollen limitation increased and reproduction eventually failed. Th ese results support the hypothesis that pollinators can act as important biotic fi lters infl uencing plant distribution, and warn against predictions of geographical range shifts based solely on climatic variables.